An Exploratory Look into the Entrepreneurial Competencies of Women Owners of Food Processing Businesses in Bacolod City - Magada, Ma. Fara J. (Philippine Social Sciences Review; PSSR Vol. 69 No. 1 2017, Ed. Rogelio Alicor L. Panao, 2018)
This study looks into the entrepreneurial competencies of Filipino women using a narrow sample comprised of owners of food processing establishments in Bacolod City, Negros Occidental. It argues that women’s business owners’ capacity to hone business competencies is related to presence of opportunity, relationship, and personal characteristics such as creativity and openness to new learning. The study seeks to determine whether there are differences across women entrepreneurs based on their personality types and line of business. Results suggest that women are generally competent in achieving short term goals. However, women business owners who are not over 45 years old, as well as those with under 10 years of experience, appear to show more commitment to their enterprises. Surprisingly, entrepreneurs who have had no prior business training appear to exhibit better analytical skills than their counterparts. Operators of medium scale enterprises, on the other hand, manifest stronger personal resilience.
Keywords: Bacolod City, entrepreneurial competencies, food processing business, Micro Small Medium Enterprise (MSME), women owners